Nanoflower synthesis, characterization and analytical applications: a review - Chormey, Dotse Selali; Erarpat, Sezin; Zaman, Buse Tugba; Ozdogan, Nizamettin; Yagmuroglu, Ozan; Bakirdere, Sezgin (SPRINGER HEIDELBERG, 2023)
The occurrence of contaminants in the environment requires very sensitive analytical techniques for their determination. For that, analytical techniques have been recently improved by nanotechnologies. Here, we review nanoflowers, which are nanomaterials with flower-like morphologies, with focus on their synthesis, characterization and analytical applications. Synthesis methods include coprecipitation, sol-gel, solvothermal, hydrothermal, chemical vapor deposition, microwave-assisted, electrochemistry, sonochemistry and biosynthesis. Characterization can be done by microscopy, e.g., scanning electron, transmission electron and atomic force; by spectroscopy, e.g., ultraviolet-visible, Raman, Fourier transform infrared, atomic absorption spectrophotometry, dynamic light scattering and mass spectrometry; by chromatography, e.g., liquid, hydrodynamic and gel permeation; by X-ray fluorescence, diffraction and photoelectron spectroscopy; and by thermal gravimetry, differential centrifugal sedimentation and nanoparticle tracking analysis. Analytical applications include nanoflowers coupled to chromatography or sensors to detect organic and inorganic compounds. Nanoflowers are easy to prepare, and they display high surface area, high efficiency, high stability and cost-effectiveness.
Keywords: Adsorbent; Analytical sensors; Chromatography; Microextraction; Nanoflowers; Nanoparticles; SOLID-PHASE EXTRACTION; ZNO NANOFLOWERS; GREEN SYNTHESIS; STRIPPING VOLTAMMETRY; HYBRID NANOFLOWERS; METAL-IONS; REMOVAL; GOLD; Chemistry; Engineering; Environmental Sciences & Ecology